The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.rmed.2020.106023
|View full text |Cite
|
Sign up to set email alerts
|

D-dimer in patients infected with COVID-19 and suspected pulmonary embolism

Abstract: To analyze the risk factors for pulmonary embolism (PE) in patients infected with COVID-19. Methods: We conducted an observational, retrospective study. Patients with severe infection with COVID-19 and suspected PE were included. Results: Patients with higher levels of D-dimer and those requiring intubation were at a higher risk of developing PE. Higher D-dimer levels were associated with a greater probability of PE 3, 6, 9 and 12 days after determining D-dimer levels with an OR of 1.7, 2.0, 2.4 and 2.4, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
68
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 10 publications
11
68
2
4
Order By: Relevance
“…Several studies have described an association between the severity of the disease and high D-dimer [4][5][6]. Patients with severe COVID-19 disease with high D-DIMER level have an increased risk of developing pulmonary embolism [17]. In our study, there is significant association of high D-DIMER level in ICU group.…”
Section: Discussionsupporting
confidence: 57%
“…Several studies have described an association between the severity of the disease and high D-dimer [4][5][6]. Patients with severe COVID-19 disease with high D-DIMER level have an increased risk of developing pulmonary embolism [17]. In our study, there is significant association of high D-DIMER level in ICU group.…”
Section: Discussionsupporting
confidence: 57%
“…High fibrin degradation leads to elevated levels of fibrinogen and D-dimer 70 , which might also explain the occurrence of venous thromboembolism in critical patients of COVID-19 71 . In addition, a study with a short follow-up period also reported the existence of a dynamic correlation between the D-dimer levels and the severity of COVID-19 72 . Furthermore, pulmonary embolism and deep vein thrombosis were also observed in patients with severe COVID-19 73 , 74 , which suggests that D-dimer might play a prominent role in governing the severity of COVID-19 patients.…”
Section: Discussionmentioning
confidence: 93%
“…These molecules may also be significantly dysregulated in patients with COVID-19, as reviewed in the introduction. Specifically, dysregulation during COVID-19, has been noted in P-selectin [8], fibrinogen and D-dimer [4,5,[9][10][11][12][13][14][15], and vWF [16,17]. Depending on the direction, dysregulation of fibrin(ogen) D-Dimer, VWF and P-selectin may result in either hypercoagulation or excessive bleeding and thrombocytopenia.…”
Section: Resultsmentioning
confidence: 99%
“…During COVID-19 pathology, depending on the severity of the condition, dysregulation has been noted in all of the mentioned biomarkers, where increased levels of P-selectin [8], fibrinogen and Ddimer accompany COVID-19 progression [4,5,[9][10][11][12][13][14][15] and vWF [16,17] have been found. D-dimers are normally not present in blood unless coagulation has occurred, and the D-dimer therefore serves as a biomarker for thrombosis [18,19].…”
Section: Introductionmentioning
confidence: 99%